Alternative schooling and school choice. - Osborne, Allan G., Jr., 1951-; Russo, Charles J.; Cattaro, Gerald Michael (Debating issues in American education ;, 2012)
Contributors explore such varied issues as charter schools, for-profit schools, faith-based schools, magnet schools, vouchers, and more. Each chapter opens with an introductory essay by the volume editor, followed by point/counterpoint articles written and signed by invited experts, and concludes with Further Readings and Resources.